Prediction of the Pharmacokinetic Drug Interactions of Direct Oral Anticoagulants Using Mechanistic Static Modelling - Schaat, Mostafa (My University, 2024)
Background Direct oral anticoagulants are cardiovascular drugs used in the clinical treatment and prevention of thromboembolism. Pharmacokinetic drug interactions may cause a decrease or several-fold increases in their exposure leading to unfavourable therapeutic outcomes. Methods In this study, the author predicts pharmacokinetic drug interactions of four direct oral anticoagulants as interaction objects using static mechanistic modelling. The author additionally presents an adjusted method for predicting the fractions transported of drug interaction objects by drug transporters in vivo. The method is straightforward and relies on existing clinical drug interaction results, transporter and enzyme assay results in vitro of an interaction precipitant, and mass-balance findings of the drug under study. Finally, this article aims to further streamline static mechanistic modelling by standardising the method’s terminology. Results Using the fractions transported predicted by the adjusted method, the author predicted 34 drug interaction signals involving direct oral anticoagulants as objects. Twenty-five of the modelled 34 interactions predicted increases greater than 1.25 folds, of which four interactions predicted increases greater than 2 folds. The latter were interactions of dabigatran etexilate with diltiazem, cyclosporine, dronedarone, and quinidine in increasing order of magnitude. The remaining nine simulations indicated little to no increases. Conclusion The identified predictions will serve as cues for the further investigation of their drug interactions, taking into consideration the limitations and prospects of the method used in this study.
Keywords: Pharmacokinetics, Drug Interactions, Direct Acting Oral Anticoagulants, In silico Models